2020
DOI: 10.1039/c9ra09348f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new piperazinyl-pyrrolo[1,2-a]quinoxaline derivatives as inhibitors of Candida albicans multidrug transporters by a Buchwald–Hartwig cross-coupling reaction

Abstract: Two series of piperazinyl-pyrrolo[1,2-a]quinoxaline derivatives were prepared via a Buchwald-Hartwig cross-coupling reaction and then evaluated for their ability to inhibit the drug efflux activity of CaCdr1p and CaMdr1p transporters of Candida albicans overexpressed in a Saccharomyces cerevisiae strain. In the initial screening of twenty-nine piperazinyl-pyrrolo[1,2-a]quinoxaline derivatives, twenty-three compounds behaved as dual inhibitors of CaCdr1p and CaMdr1p. Only four compounds showed exclusive inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Quinoxaline bearing piperazinyl moieties were identified as dual inhibitors of CaCdr1 and CaMdr1 overexpressed in a Saccharomyces cerevisiae strain (Guillon et al, 2020).…”
Section: Piperazinyl-quinoxaline Derivativesmentioning
confidence: 99%
“…Quinoxaline bearing piperazinyl moieties were identified as dual inhibitors of CaCdr1 and CaMdr1 overexpressed in a Saccharomyces cerevisiae strain (Guillon et al, 2020).…”
Section: Piperazinyl-quinoxaline Derivativesmentioning
confidence: 99%
“…Extensive state-of-the-art studies revealed a lack of methods to achieve their construction, even though their synthesis might be of interest in medicinal chemistry. Indeed, the tricyclic quinoxaline-containing compounds are widespread in a variety of therapeutic agents such as anti-HIV [10], antiparasitic [11][12][13][14], and antitumoral [15] (Figure 1), and make our new condensed cyclic systems promising candidates for diverse uses. To the best of our knowledge, the derivatives of which the synthesis was pursued are unknown compounds with a rather infrequently reported heterocyclic core [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…2 For instance, the piperazinyl-pyrrolo [1,2-a]quinoxaline derivatives could be used as inhibitors of Candida albicans multidrug transporters. 3 Therefore, the development of facile and direct methods for the assembly of the kind of valuable heterocycles is of great significance.…”
mentioning
confidence: 99%
“… Moreover, the privileged compounds are frequently applied as key intermediates or precursors to build other useful heterocycles possessing interesting biological activities . For instance, the piperazinyl-pyrrolo­[1,2- a ]­quinoxaline derivatives could be used as inhibitors of Candida albicans multidrug transporters . Therefore, the development of facile and direct methods for the assembly of the kind of valuable heterocycles is of great significance.…”
mentioning
confidence: 99%